Palaeoenvironmental Interpretation of Yedoma Silt (Ice Complex) Deposition as Cold‐Climate Loess, Duvanny Yar, Northeast Siberia. (July 2015) - Murton, Julian B.; Goslar, Tomasz; Edwards, Mary E.; Bateman, Mark D.; Danilov, Petr P.; Savvinov, Grigoriy N.; Gubin, Stanislav V.; Ghaleb, Bassam; Haile, James; Kanevskiy, Mikhail; Lozhkin, Anatoly V.; Lupachev, Alexei V.; et al.
Abstract Uncertainty about the geological processes that deposited syngenetically frozen ice‐rich silt (yedoma) across hundreds of thousands of square kilometres in central and northern Siberia fundamentally limits our understanding of the Pleistocene geology and palaeoecology of western Beringia, the sedimentary processes that led to sequestration of hundreds of Pg of carbon within permafrost and whether yedoma provides a globally significant record of ice‐age atmospheric conditions or just regional floodplain activity. Here, we test the hypotheses of aeolian versus waterlain deposition of yedoma silt, elucidate the palaeoenvironmental conditions during deposition and develop a conceptual model of silt deposition to clarify understanding of yedoma formation in northern circumpolar regions during the Late Pleistocene. This is based on a field study in 2009 of the Russian stratotype of the 'Yedoma Suite', at Duvanny Yar, in the lower Kolyma River, northern Yakutia, supplemented by observations that we have collected there and at other sites in the Kolyma Lowland since the 1970s. We reconstruct a cold‐climate loess region in northern Siberia that forms part of a vast Late Pleistocene permafrost zone extending from northwest Europe across northern Asia to northwest North America, and that was characterised by intense aeolian activity. Five litho‐ and cryostratigraphic units are identified in yedoma remnant 7E at Duvanny Yar, in ascending stratigraphic order: (1) massive silt, (2) peat, (3) stratified silt, (4) yedoma silt and (5) near‐surface silt. The yedoma silt of unit 4 dominates the stratigraphy and is at least 34 m thick. It is characterised by horizontal to gently undulating subtle colour bands but typically lacks primary sedimentary stratification. Texturally, the yedoma silt has mean values of 65 ± 7 per cent silt, 15 ± 8 per cent sand and 21 ± 4 per cent clay. Particle size distributions are bi‐ to polymodal, with a primary mode of about 41 μm (coarse silt) and subsidiary modes are 0.3–0.7 μm (very fine clay to fine clay), 3–5 μm (coarse clay to very fine silt), 8–16 μm (fine silt) and 150–350 μm (fine sand to medium sand). Semidecomposed fine plant material is abundant and fine in‐situ roots are pervasive. Syngenetic ice wedges, cryostructures and microcryostructures record syngenetic freezing of the silt. An age model for silt deposition is constructed from 47 pre‐Holocene accelerator mass spectrometry (AMS) 14C ages, mostly from in‐situ roots and from three optically stimulated luminescence (OSL) ages of quartz sand grains. The 14C ages indicate that silt deposition extends from 19 000 ± 300 cal BP to 50 000 cal BP or beyond. The OSL ages range from 21.2 ± 1.9 ka near the top of the yedoma to 48.6 ± 2.9 ka near the bottom, broadly consistent with the 14C age model. Most of the yedoma silt in unit 4 at Duvanny Yar constitutes cryopedolith (sediment that has experienced incipient pedogenesis along with syngenetic freezing). Mineralised and humified organic remains dispersed within cryopedolith indicate incipient soil formation, but distinct soil horizons are absent. Five buried palaeosols and palaeosol 'complexes' are identified within cryopedolith on the basis of sedimentary and geochemical properties. Magnetic susceptibility, organic content, elemental concentrations and ratios tend to deviate from average values of these parameters at five levels in unit 4. The cryopedolith‐palaeosol sequence accreted incrementally upwards on a vegetated palaeo‐land surface with a relief of at least several metres, preserving syngenetic ground ice in the aggrading permafrost. Pollen spectra dated to between about 17 000 and 25 000 14C BP characteristically have frequencies of 20–60 per cent tree/shrub pollen (mainly Betula and Pinus) and 20–60 per cent graminoids, predominantly Poaceae, plus forbs, whereas spectra dated to about 30 000–33 000 14C BP have lower values of woody taxa (about 10%) and are dominated by graminoids (mainly Poaceae), forbs (particularly Caryophyllaceae and Asteraceae) and Selaginella rupestris. The latter are more typical of Last Glacial Maximum (LGM) samples reported elsewhere in Siberia, and the unusually high arboreal pollen values in the LGM yedoma at Duvanny Yar are attributed to long‐distance transport of pollen. Three hypotheses concerning the processes and environmental conditions of yedoma silt deposition at Duvanny Yar are tested. The alluvial‐lacustrine hypothesis and the polygenetic hypothesis are both discounted on sedimentary, palaeoenvironmental, geocryological and palaeoecological grounds. The loessal hypothesis provides the only reasonable explanation to account for the bulk of the unit 4 yedoma silt at this site. Supporting the loessal interpretation are sedimentological and geocryological similarities between the Duvanny Yar loess‐palaeosol sequence and cold‐climate loesses in central and northern Alaska, the Klondike (Yukon), western and central Siberia and northwest Europe. Differences between loess at Duvanny Yar and that in western and central Siberia and northwest Europe include the persistence of permafrost and the abundance of ground ice and fine in‐situ roots within the yedoma. Modern analogues of cold‐climate loess deposition are envisaged at a local scale in cold, humid climates where local entrainment and deposition of loess are generally restricted to large alluvial valleys containing rivers that are glacially sourced or drain areas containing Late Pleistocene glacial deposits, and thus glacially ground silt. The Duvanny Yar yedoma shares sedimentological and geocryological features with yedoma interpreted as ice‐rich loess or reworked loess facies at Itkillik (northern Alaska) and in the central Yakutian lowland, and with yedoma in the Laptev Sea region and the New Siberian Archipelago. It is therefore suggested that many lowland yedoma sections across Beringia are primarily of aeolian origin (or consist of reworked aeolian sediments), although other depositional processes (e.g. alluvial and colluvial) may account for some yedoma sequences in river valleys and mountains. A conceptual model of yedoma silt deposition at Duvanny Yar as cold‐climate loess in Marine Isotope Stage (MIS) 3 and MIS 2 envisages summer or autumn as the main season of loess deposition. In summer, the land surface was snow‐free, unfrozen and relatively dry, making it vulnerable to deflation. Graminoids, forbs and biological soil crust communities trapped and stabilised windblown sediments. Loess accretion resulted from semicontinuous deposition of fine background particles and episodic, discrete dust storms that deposited coarse silt. Winter was characterised by deep thermal contraction cracking beneath thin and dusty snow covers, and snow and frozen ground restricted deflation and sediment trapping by dead grasses. Sources of loess at Duvanny Yar potentially include: (1) sediments and weathered bedrock on uplands to the east, south and southwest of the Kolyma Lowland; (2) alluvium deposited by rivers draining these uplands; and (3) sediments exposed in the Khallerchin tundra to the north and on the emergent continental shelf of the East Siberian Sea. Glacially sourced tributaries of the palaeo‐Kolyma River contributed glacially ground silt into channel and/or floodplain deposits, and some of these were probably reworked by wind and deposited as loess in the Kolyma Lowland. The palaeoenvironmental reconstruction of the sedimentary sequence at Duvanny Yar is traced from MIS 6 to the late Holocene. It includes thermokarst activity associated with alas lake development in the Kazantsevo interglacial (MIS 5e), loess accumulation, pedogenesis and syngenetic permafrost development, possibly commencing in the Zyryan glacial (70 000–55 000 cal BP) and extending through the Karginsky interstadial (55 000–25 000 cal BP) and Sartan glacial (25 000–15 000 cal BP), cessation of yedoma silt deposition during the Lateglacial, renewed thermokarst activity in the early Holocene, and permafrost aggradation in the mid to late Holocene. Beringian coastlands from northeast Yakutia through the north Alaskan Coastal Plain to the Tuktoyaktuk Coastlands (Canada) were characterised by extensive aeolian activity (deflation, loess, sand dunes, sand sheets, sand wedges) during MIS 2. Siberian and Canadian high‐pressure cells coupled with a strengthened Aleutian low‐pressure cell would have created enhanced pressure gradient‐driven winds sufficient to entrain sediment on a regional scale. Summer winds are thought to have deflated sediment exposed on the East Siberian Sea shelf and deposited silt as a distal aeolian facies to the south. Additionally, stronger localised winds created by local downslope gravity flows (katabatic winds) may have entrained sediment. Local katabatic winds in summer may have transported silt generally northwards towards the Kolyma Lowland, particularly during times of extended upland glaciation in the North Anyuy Range to the east during the Zyryan (MIS 4) period, whereas winter winds carried limited amounts of silt generally southwards as a result of pressure gradient forces. The Duvanny Yar yedoma is part of a subcontinental‐scale region of Late Pleistocene cold‐climate loess. One end member, exemplified by the yedoma at Duvanny Yar, was loess rich in syngenetic ground ice (Beringian yedoma). The other, exemplified by loess in northwest Europe, was ice‐poor and subject to complete permafrost degradation at the end of the last ice age. These end members reflect a distinction between enduring cold continuous permafrost conditions leading to stacked ice‐rich transition zones and large syngenetic ice wedges in much of Beringia versus conditions oscillating between cold permafrost, warm permafrost and seasonal frost, leading to repeated permafrost thaw and small ice‐wedge pseudomorphs in northwest Europe. Copyright © 2015 John Wiley & Sons, Ltd.